Microwave-Assisted Extraction Of Polysaccharide From Cinnamomum Cassia With Anti-Hyperpigmentation Properties - Salem, Al Ajalein Alhareth Abdulraheem (2023)
Polysaccharides with anti-hyperpigmentation properties have not been reported elsewhere. The current study extracted the polysaccharides from Cinnamomum cassia bark using microwave-assisted approach, and optimized the extraction parameters (i.e. microwave power, irradiation time and buffer-to-sample (B:S) ratio) based on Box-Behnken design to obtain polysaccharides with high anti-hyperpigmentation activities, antioxidant activity, sun protection factor (SPF) as well as the extraction yield.